COMMUNITY PREPAREDNESS AND AWARENESS ON WATER RELATED DISASTERS IN RAUB, PAHANG - Norhazlina Fairuz Musa Kutty; Iddi Kifla Mohd Taib; Nik Rasheed Ismail; Wan Farizatul Shima Wan Ahmad Fakuradzi, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Water is essential for all living things. But water also prone to the risk of water related disaster which is not a new phenomenon that happened worldwide including Malaysia. Despite disasters always associated with natural catastrophe, disaster can be classified into three categories namely natural, man-made and hybrid disasters. Notwithstanding the category of disasters, the impact of it would cause loss of lives, damage to property or the environment as well as affecting the daily activities of local community. Therefore, this research aims to identify the issues related to water related disaster among community in Raub, Pahang, examine the level of knowledge that affects community preparedness and awareness, community participation and empowerment of the community in creating resiliency towards water related disasters, and finally to propose a framework of community resiliency to water related disasters in Raub, Pahang. In achieving the objectives, qualitative research methods were adopted using face to face interview and qualitative online survey using semi structured interview protocols. This research found that past and present experience by the community had imparted a good understanding of water scarcity among the community in Raub. However, their preparedness level to be independent in dealing with the risk of water scarcity is still low as they had few constraints to establish a more structured water scarcity management system with less dependence on the government’s assistance.